2015
DOI: 10.1038/npp.2015.128
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroimaging-Aided Prediction of the Effect of Methylphenidate in Children with Attention-Deficit Hyperactivity Disorder: A Randomized Controlled Trial

Abstract: Although methylphenidate hydrochloride (MPH) is a first-line treatment for children with attention-deficit hyperactivity disorder (ADHD), the non-response rate is 30%. Our aim was to develop a supplementary neuroimaging biomarker for predicting the clinical effect of continuous MPH administration by using near-infrared spectroscopy (NIRS). After baseline assessment, we performed a double-blind, placebo-controlled, crossover trial with a single dose of MPH, followed by a prospective 4-to-8-week open trial with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
(45 reference statements)
0
30
0
Order By: Relevance
“…ADHD is characterized by the persistent symptoms of inattention, hyperactivity, and impulsivity ( Faraone et al, 2005 ). By using behavioral tasks requiring attentiveness and concentration, fNIRS imaging has demonstrated that these ADHD-related symptoms are associated with low cerebral cortical activity in a number of regions, including the PFC, inferior prefrontal gyrus, middle prefrontal gyrus, supra-marginal gyrus, and angular gyrus ( Araki et al, 2015 ; Ichikawa et al, 2014 ; Inoue et al, 2012 ; Ishii-Takahashi et al, 2015 ; Kochel et al, 2015 ; Monden et al, 2015 ; Moser et al, 2009 ; Nagashima et al, 2014a ; 2014b ; 2014c ; Negoro et al, 2010 ; Schecklmann et al, 2011b ; Tsujimoto et al, 2013 ; Weber et al, 2005 ; Xiao et al, 2012 ; Yasumura et al, 2014 ). Similarly, frontal hypoactivity has been observed in ASD patients during behavioral tasks designed to assess social relations and communicative abilities that are dysfunctional or inappropriate in these patients ( Iwanaga et al, 2013 ; Kajiume et al, 2013 ; Kita et al, 2011 ; Kuwabara et al, 2006 ; Minagawa-Kawai et al, 2009 ; Tamura et al, 2012 ; Xiao et al, 2012 ; Yasumura et al, 2014 ).…”
Section: Applications Of Fnirs To Human Subjectsmentioning
confidence: 99%
“…ADHD is characterized by the persistent symptoms of inattention, hyperactivity, and impulsivity ( Faraone et al, 2005 ). By using behavioral tasks requiring attentiveness and concentration, fNIRS imaging has demonstrated that these ADHD-related symptoms are associated with low cerebral cortical activity in a number of regions, including the PFC, inferior prefrontal gyrus, middle prefrontal gyrus, supra-marginal gyrus, and angular gyrus ( Araki et al, 2015 ; Ichikawa et al, 2014 ; Inoue et al, 2012 ; Ishii-Takahashi et al, 2015 ; Kochel et al, 2015 ; Monden et al, 2015 ; Moser et al, 2009 ; Nagashima et al, 2014a ; 2014b ; 2014c ; Negoro et al, 2010 ; Schecklmann et al, 2011b ; Tsujimoto et al, 2013 ; Weber et al, 2005 ; Xiao et al, 2012 ; Yasumura et al, 2014 ). Similarly, frontal hypoactivity has been observed in ASD patients during behavioral tasks designed to assess social relations and communicative abilities that are dysfunctional or inappropriate in these patients ( Iwanaga et al, 2013 ; Kajiume et al, 2013 ; Kita et al, 2011 ; Kuwabara et al, 2006 ; Minagawa-Kawai et al, 2009 ; Tamura et al, 2012 ; Xiao et al, 2012 ; Yasumura et al, 2014 ).…”
Section: Applications Of Fnirs To Human Subjectsmentioning
confidence: 99%
“…Thus, the FTO genotype-related increase in BMI in adolescence and young adulthood would be essential for physical development, which could lead to or result from better psychological health. Second, the rs9939609 A allele is protective of child emotional problems and attention deficits and hyperactivity disorder symptoms 65 , which is thought to be due to an altered reward response in dopaminergic neuron in the prefrontal cortex 66 . Conversely, the mouse knock-out FTO gene within the midbrain dopaminergic system showed hyperactivity and aberrant sensitivity to dopamine stimulants 23 .…”
Section: Discussionmentioning
confidence: 99%
“…27 A longitudinal study showed that ADHD patients exhibited improved prefrontal responses after a single dose of methylphenidate, and its long-term use yielded an activation equivalent to that of a healthy person. 61…”
Section: Stop-signal Taskmentioning
confidence: 99%